Experimental and Numerical Study of the Heat Dissipation of the Electronic Module in an Air Conditioner Outdoor Unit - Yi Peng; Su Du; Qingfeng Bie; Dechang Wang; Qinglu Song; Sai Zhou (Energies)
Effective thermal management of electronic modules is crucial to the reliable operation of variable frequency air conditioners. For this reason, two types of plate-finned heat sinks of electronic modules were selected. The experiments utilized ceramic heating plates to simulate chip heating, conducted in an enthalpy difference laboratory with controlled environments. Four installation cases were analyzed to evaluate the impact of heat sink orientation, airflow direction, and structural layout. The results showed that when multiple chips were arranged on the same heat dissipation substrate, the heat dissipation process of the chips would be coupled with each other, and the rational layout of the chips played an important role in heat dissipation. In the case of cooling air impacting the jet, the heat dissipation performance of the heat sink was significantly improved, and the heat transfer coefficient of the heat sink was as high as 316.5 W·m−2·°C−1, representing a 6.9% improvement over conventional designs (case I: 296.1 W·m⁻2·°C⁻1). The maximum temperature of the chips could be reduced by 11.1%, which is 10.1 °C lower. This study will provide a reference for the optimization design of the heat sink of the electric control module in inverter air conditioners.